Construction of a Synthetic Earth Gravity Model by Forward Gravity Modelling - Kuhn, Michael; Featherstone, Will (Springer, 2005)
A synthetic Earth gravity model (SEGM) generates exact gravity field quantities and therefore is well suited to validate methods used in gravity field modelling. This paper describes the construction of a SEGM by forward gravity modelling using available data describing the Earth's mass distribution. In particular, the global 5-arc-min x 5-arc-min JGP95E digital elevation model (DEM), the most recent global compilation of crustal thickness and mass heterogeneities (CRUST2.0) and the S12WM13 mantle model of seismic velocity anomalies have been used. Results for the SEGM show in general a good agreement with the anomalous Earth's gravity field (geoid height). However,in some areas the differences with respect to the observed gravity field almost reach the magnitude of the geoid height itself. Possible explanations can be un-modelled mass anomalies situated in the upper and middle mantle.